Gastroenteric parasite of wild Galliformes in the Italian Alps: implication for conservation management. Issue 4 (19th April 2020) - Fanelli, A.; Menardi, G.; Chiodo, M.; Giordano, O.; Ficetto, G.; Bessone, M.; Lasagna, A.; Carpignano, M.G.; Molinar Min, A.; Gugiatti, A.; Meneguz, P.G.; Tizzani, P.
Abstract: This study provides insights about the diversity, prevalence and distribution of alpine wild galliformes gastrointestinal parasite community, trying to fill a gap in the scientific information currently available in scientific literature. The analysis included three host species: 77 rock partridge ( Alectoris graeca saxatilis ), 83 black grouse ( Tetrao tetrix tetrix ) and 26 rock ptarmigan ( Lagopus muta helveticus ) shot during the hunting seasons 2008–2015. Parasites isolated were Ascaridia compar, Capillaria caudinflata and cestodes. The rock ptarmigan was free from gastrointestinal parasites, whereas the most prevalent helminth (37%) was A. compar in both black grouse and rock partridge. C. caudinflata occurrence was significantly higher in black grouse (prevalence = 10%, mean abundance = 0.6 parasites/sampled animal) than in rock partridge (prevalence = 1.20%, mean abundance = 0.01 parasites/sampled animal). Significant differences were detected among hunting districts. A. compar was found with a significant higher degree of infestation in the hunting districts in the northern part of the study area whereas cestodes abundance was higher in Lanzo Valley. Quantitative analysis of risk factors was carried out using a generalized linear model (GLM) only on the most common parasite ( A. compar ). Latitude was the only factors associated with infestation risk (OR = 52.4). This study provides information on the composition and variability of the parasite community in the alpine Galliformes species.